2013
DOI: 10.26740/jptt.v4n1.p24-30
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pola Asuh Dan Ekspresi Emosi Keluarga Dengan Kekambuhan Pasien Skizofrenia Di Rumah Sakit Jiwa Menur Surabaya

Abstract: Schizophrenia is classified in severe mental disorders so that the possibility to recover from it is fairly minimal. Based on a study, 80% of schizophrenic patients experienced a relapse from schizophrenia and only about 20% of patients declared recovered on pre-morbid level (Arif, 2006). Many cases of relapse occurred when the patient returned to their family. Some studies suggest that the factor of interaction patterns within the family, such as parenting and emotional expression among the members of family,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
2
7
0
2
Order By: Relevance
“…Research conducted by Darwin et al in 2013 in Jakarta showed a significant relationship between the care burden with the expressed emotion in the family of schizophrenic patients (p < 0.001) [6]. The study conducted by Carla and his friends in 2012 in Italy, also shows the great reality in southern Europe that there is a relationship between the expressed emotion of a high caregiver with a subjective burden [10].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Research conducted by Darwin et al in 2013 in Jakarta showed a significant relationship between the care burden with the expressed emotion in the family of schizophrenic patients (p < 0.001) [6]. The study conducted by Carla and his friends in 2012 in Italy, also shows the great reality in southern Europe that there is a relationship between the expressed emotion of a high caregiver with a subjective burden [10].…”
Section: Introductionmentioning
confidence: 94%
“…High burden and stress on families who care for patients have been reported subjectively and this has led to the emergence of high emotion. Strong family ties can seem to reduce the care burden that affects family emotion [6]. High expression emotion in families with chronic disease seems to be more related to direct personal reactions and responsibilities in care, especially in the first episode psychosis.…”
Section: The Relationship Between the Care Burden And Expressed Emotion In Schizophrenia Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semua bahasa di dunia ini, tentu mempunyai unsur emosi yang berkaitan dengan ucapan atau tuturan penuturnya (Handayani & Nurwidawati, 2013). Tindak tutur menjadi dasar analisis aspek pragmatik yang lain seperti praanggapan, perikutan, implikatur percakapan, prinsip kerja sama, dan prinsip kesantunan (Handono, 2017).…”
Section: Pendahuluanunclassified
“…Two factors influence stress, namely, biological factors (e.g., heredity, physical condition) and sociocultural factors (e.g., personality development, experience, and other conditions) (Wood et al, 2016;Strohmeier et al, 2018). Handayani and Nurwidawati (2013) showed that the family's emotions toward the situation and lack of understanding in how to care for family members with mental disorders cause recurrence. Sitinjak (2016) found that 70% of families dealing with a mentally ill patient experience moderate anxiety when the patient relapses.…”
Section: Introductionmentioning
confidence: 99%